Identifying Justice: The Economic Way Out - Karki, Adity (Kathmandu School of Law Review, 2012)
The essay titles as "Identifying Justice: The Economic Way Out" deals with trafficking problem of young girls and women in Nepal. In the essay, an attempt is made to discover the core reason behind the trafficking problem of Nepal. Also, the essay discusses whether the justice provided to victims of trafficking is itself just or not? What are the legal provisions of Nepal that deals with trafficking issues of Nepal? Despite of the legal provisions, why trafficking is still not controlled by the authority? The essay aims to solve these questions. As a result, poor economic circumstances come forward as the root-problem which ultimately brings many other problems in the society. The essay suggests the idea that the victim of trafficking is not only a particular woman or girl but also the entire society. Finally, in the later part of the essay, some alternative way outs are suggested that would help to minimize trafficking problem in Nepal.